MODEL PEMBELAJARAN TWO-STAY TWO-STRAY (TS-TS) UNTUK MENINGKATKAN HASIL BELAJAR DAN SIKAP KERJASAMA SISWA - Nurhayati, Nenih; Fahri, Muhammad (ATTA`DIB, 2019)
Learning is a formal activity carried out at school. In this case the occurrence of an interaction between students, teachers and their environment. The role of a teacher is very important, it will greatly affect the learning outcomes and student development. This study aims to determine the application of a two-stray two-stay learning model that can improve learning outcomes and students' cooperative attitudes in fourth grade science subjects MI Jam’iyatul Falah Bojong Gede Bogor Regency. The method used is classroom action research using the Kemmis Mc. Taggart model consisting of planning, implementation, observation and reflection. The results showed that student learning outcomes in pre-cycle with completeness percentage value of 56.25%, in cycle one the completeness percentage value was 75%, then in cycle two the completeness percentage value was 87.5%. The attitude of student collaboration on pre cycle average value of 2.45 with sufficient category, in cycle one the average value is 2.85 with good category, and in cycle two the average value is 3.5 with a very good category. This the application of a two-stray two-stay learning model can improve learning outcomes and the cooperative attitude of students in fourth grade science subjects in MI Jam'iyatul Falah Bojong Gede Bogor Regency.